THE EFFECT OF FISCAL SERVICES, TAX LITERACY, AND INTRINSIC MOTIVATION ON TAXPAYER COMPLIANCE WITH TAX SANCTIONS AS A MODERATING VARIABLE - Nur Azizah Taslim HS; Andi Kusumawati; Amiruddin (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2025)
Motor vehicle tax serves as a significant source of local revenue, facilitating local development and the maintenance of public infrastructure. In Central Mamuju Regency, taxpayer compliance remains notably low, with over 26,000 vehicles reported as being in arrears in 2023. This research investigates the impact of tax officer service quality, tax literacy, and intrinsic motivation on taxpayer compliance, considering tax sanctions as a moderating variable. This study utilises Attribution Theory and the Theory of Planned Behaviour, focussing on the internal and external factors influencing compliance behaviour. A total of 100 respondents were selected via the Slovin formula, and the data were analysed using multiple linear regression and Moderated Regression Analysis (MRA) with SPSS version 26. The findings indicated that tax officer services and intrinsic motivation significantly influenced compliance, whereas tax literacy did not demonstrate a significant effect. Additionally, tax sanctions enhance the impact of tax officer services and intrinsic motivation on compliance; however, they do not influence the relationship between tax literacy and compliance. This study emphasises the necessity of integrating quality public services with initiatives aimed at enhancing taxpayers' intrinsic motivation, alongside the equitable enforcement of tax sanctions.